2015
DOI: 10.12944/cwe.10.special-issue1.87
|View full text |Cite
|
Sign up to set email alerts
|

High Occurrence of Potentially Pathogenic Free Living Amoebae in Water Bodies of Kaleybar and Khodaafarin, East Azerbaijan Province

Abstract: Free living amoebas are widespread protozoans that can be found in different environmental resources such as water bodies, soil and clays. Free living amoebae particularly Acanthamoeba could lead to diseases with poor prognosis including ameobic keratitis (AK) and granulomatous amebic encephalitis (GAE) especially in contact lens wears and immunocompromised individuals, respectively. In the present study 50 samples were collected from water resources (hot-springs, cold springs, rivers, wells, refined drinking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…in water resources of different parts of the country. 34,35 Some previousstudies have reported the presence of FLA in hot springs, particularly two studies that were carried out in Ardebil Province. 36,37 Acanthamoeba spp.…”
Section: Discussionmentioning
confidence: 99%
“…in water resources of different parts of the country. 34,35 Some previousstudies have reported the presence of FLA in hot springs, particularly two studies that were carried out in Ardebil Province. 36,37 Acanthamoeba spp.…”
Section: Discussionmentioning
confidence: 99%